2000
DOI: 10.1128/iai.68.11.6223-6232.2000
|View full text |Cite
|
Sign up to set email alerts
|

Lack of CD4+T Cells Does Not Affect Induction of CD8+T-Cell Immunity againstEncephalitozoon cuniculiInfection

Abstract: Cell-mediated immunity has been reported to play an important role in defense against Encephalitozoon cuniculi infection. Previous studies from our laboratory have underlined the importance of cytotoxic CD8 ؉ T lymphocytes (CTL) in survival of mice infected with E. cuniculi. In the present study, immune response against E. cuniculi infection in CD4؉ T-cell-deficient mice was evaluated. Similar to resistant wild-type animals, CD4 ؊/؊ mice were able to resolve E. cuniculi infection even at a very high challenge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 39 publications
3
37
0
Order By: Relevance
“…Coordinated interaction between CD4 ϩ and CD8 ϩ T cells was required to resolve an infection with the intracellular bacterium Listeria monocytogenes (44). However, the absence of CD4 ϩ T cells did not affect the CD8 ϩ -T-cell response against an Encephalitozoon cuniculi infection (31). Similar to these findings, our findings showed that a CD8…”
Section: The Role Of Conventional Cd4supporting
confidence: 81%
“…Coordinated interaction between CD4 ϩ and CD8 ϩ T cells was required to resolve an infection with the intracellular bacterium Listeria monocytogenes (44). However, the absence of CD4 ϩ T cells did not affect the CD8 ϩ -T-cell response against an Encephalitozoon cuniculi infection (31). Similar to these findings, our findings showed that a CD8…”
Section: The Role Of Conventional Cd4supporting
confidence: 81%
“…Due to their early rise, this T cell subset is an important source of cytokines, which induce the CD8 ϩ T cell response against the parasite. A recent study from our laboratory reported that adequate CD8 ϩ T cell immune response against E. cuniculi infection can be launched in CD4 ϩ T cell-deficient mice (32). These findings raised an important question about the mechanism of CD8 ϩ T cell priming in the absence of conventional CD4 ϩ T cells.…”
Section: Discussionmentioning
confidence: 84%
“…The experiment was performed twice, and the results are representative of one experiment. The importance of CD8 ϩ T cells in protection against E. cuniculi infection has been well established by studies conducted by us and in other laboratories (1,2,16,20,21). CD8 ϩ T-cell-deficient animals are highly susceptible to this pathogen, and infected mice exhibit severe morbidity before death.…”
Section: Fig 8 Augmentation Of the Il-12-mediated Cd8mentioning
confidence: 93%
“…DNA was extracted from tissues by using a DNeasy blood and tissue kit (Qiagen, Valencia CA), and 400 ng of each sample was assayed by real-time PCR using the following primers specific for E. cuniculi: ECUNF (5Ј-ATG AGAAGTGATGTGTGCG-3Ј) and ECUNR (5Ј-TGCCATGCACTCACAG GCATC-3Ј) (20). Amplification was performed with a Bio-Rad iCycler (BioRad, Hercules, CA) using the following conditions: 40 cycles of 94°C for 45 s, 53°C for 1 min, and 72°C for 30s.…”
Section: Methodsmentioning
confidence: 99%